2019
DOI: 10.1177/2396987319889468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of haemoglobin levels on outcome in intravenous thrombolysis-treated stroke patients

Abstract: Introduction Alterations in haemoglobin levels are frequent in stroke patients. The prognostic meaning of anaemia and polyglobulia on outcomes in patients treated with intravenous thrombolysis is ambiguous. Patients and methods In this prospective multicentre, intravenous thrombolysis register-based study, we compared haemoglobin levels on hospital admission with three-month poor outcome (modified Rankin Scale 3–6), mortality and symptomatic intracranial haemorrhage (European Cooperative Acute Stroke Study II-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…Most studies have shown that anemia on admission, after adjusting for various covariates including NIHSS, still predicts adverse outcomes after stroke, even in patients who have already received intravenous thrombolysis [12], except for 1 study [13]. Opposite to anemia, studies on the effect of high hemoglobin values on adverse stroke outcomes are rare and inconsistent [2, 4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have shown that anemia on admission, after adjusting for various covariates including NIHSS, still predicts adverse outcomes after stroke, even in patients who have already received intravenous thrombolysis [12], except for 1 study [13]. Opposite to anemia, studies on the effect of high hemoglobin values on adverse stroke outcomes are rare and inconsistent [2, 4].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, our study also found patients with anemia were more likely to be older, have atrial fibrillation, and have CHD [17]; high hemoglobin was more common in ever smoking and heavy alcohol patients [4] (Table 1). Also, previous studies have found that patients with anemia were more likely to have more severe stroke, and after adjusting for various covariates including NIHSS, the relative impact of anemia on poor stroke outcomes will be reduced [5, 12]. Considering the impact of NIHSS on the relationship between anemia and adverse stroke outcomes, although we have adjusted for these risk factors in our multivariable analysis, potential residual confounding effects and possible effect of comorbid disease which associated with abnormal hemoglobin values could not be completely excluded.…”
Section: Discussionmentioning
confidence: 99%
“…This may include identifying downtrends in hemoglobin (Hgb) 33,36. Although no evidence supports that anemia (less than reference values)33 is associated with hemorrhagic transformation, the overall outcomes are poorer 37. As mentioned, blood pressure stability within set parameters is important.…”
Section: Methodsmentioning
confidence: 98%
“… Intracranial or extracranial stenosis 22  Visible acute infarct 17 3) Hemodynamic instability: 1,5  Signs of active bleeding, or drop in hemoglobin 33,36,37  SBP <90 or >180 mm Hg, or out of set parameters 28,32  DBP > 105 mm Hg 1…”
Section: Development and Clinical Utility Of The Mobilization Criteri...mentioning
confidence: 99%
See 1 more Smart Citation